Toward a dynamical theory of body movement in musical performance - Demos, Alexander P.; Chaffin, Roger; Kant, Vivek (Frontiers in Psychology, 2014)
Musicians sway expressively as they play in ways that seem clearly related to the music, but quantifying the relationship has been difficult. We suggest that a complex systems framework and its accompanying tools for analyzing non-linear dynamical systems can help identify the motor synergies involved. Synergies are temporary assemblies of parts that come together to accomplish specific goals. We assume that the goal of the performer is to convey musical structure and expression to the audience and to other performers. We provide examples of how dynamical systems tools, such as recurrence quantification analysis, can be used to examine performers’ movements and relate them to the musical structure and to the musician’s expressive intentions. We show how detrended fluctuation analysis can be used to identify synergies and discover how they are affected by the performer’s expressive intentions.